MENENTUKAN POLINOMIAL MINIMAL ATAS GF p - A, Nunung; Irawanto, Bambang (MATEMATIKA, 2008)
Let  is finite field with  elements, denoted by . If  be an extension field of   and  is the algebra element of , then , polynomial of  of smallest degree such that  called minimal polynomial of . If  is primitive element, then  whose called primitive polynomial, is the minimal polynomial of  whose generate the elements of .The minimal polynomial of  whose generate the elements of  is the factor of , because the elements of  are the solution of . So, if   and  are known we have . If we factoring it, will be obtained , the minimal polynomial of  whose generate the elements of , where  is some irreducible factor in  of degree  that contain a primitive element.